Dentists' attitudes, behaviors, and barriers related to tobacco‐use cessation in the dental setting. (26th June 2012) - Prakash, Preeti; Belek, Marilynn G.; Grimes, Barbara; Silverstein, Steven; Meckstroth, Richard; Heckman, Barbara; Weintraub, Jane A.; Gansky, Stuart A.; Walsh, Margaret M.
Abstract Objective: This study assessed attitudes, behaviors, and barriers among general dentists in California, Pennsylvania, and West Virginia, related to patient tobacco cessation counseling. Methods: From 2004 to 2008, a baseline survey was mailed to 271 study dentists randomly selected from a master Delta Dental Insurance Company provider list in each state who had agreed to participate in a tobacco cessation randomized clinical trial. Four backward logistic regression models assessed correlates of the five As related to tobacco cessation: Asking about tobacco use, Advising users to quit, Assessing readiness to quit, Assisting with quitting, and Arranging follow‐up. Results: Most respondents (n = 265) were male, had practiced dentistry for over 15 years, asked about tobacco use (74%), and advised tobacco users to quit (78%). Only 19% assessed readiness to quit; 39% assisted with quitting; 4% arranged follow‐up; and 42% had formal training in tobacco cessation. Believing that tobacco cessation counseling was an important professional responsibility, practicing <15 years, and asking about tobacco use significantly related to advising users to quit. Providing cessation advice and feeling effective intervening related to assessing readiness to quit. Advising users to quit, assessing readiness to quit, feeling effective intervening, and having had formal tobacco cessation training related to assisting with quitting. Barriers to cessation counseling were perceived patient resistance (66%), lack of insurance reimbursement (56%), not knowing where to refer (49%), and lack of time (32%). Conclusion: Study dentists reported not fully performing the five As. Advising, assessing, having formal training, and feeling effective increased the likelihood of cessation counseling.